Visitors' level of awareness on safety instructions at Giant Panda Conservation Centre (GPCC), Zoo Negara, Malaysia - Siew, Kar Man; Ramachandran, Sridar; Siow, May Ling; Shuib, Ahmad; Kunasekaran, Puvaneswaran (Universiti Malaysia Sarawak, 2018)
People visiting Giant Panda in Zoo Negara Malaysia is getting more after the birth of the panda cub. Hence, in order to well manage the crowd due to the Giant Panda, the management needs to know further about the visitors’ information, interest and their behaviour. There are several aspects to discover and one of the important aspects is safety. Therefore, this study is mainly to determine the visitors’ level of awareness on safety instructions in Giant Panda Conservation Centre (GPCC), Zoo Negara. The data for this study was obtained from primary and secondary sources. Primary data is collected from the visitors coming to Giant Panda Conservation Centre (GPCC), Zoo Negara through personal interview and questionnaire. Secondary data will be from relevant journals, books, website and internet searches. Data elicitation employed a face-to-face survey approach amongst visitors to GPCC. The results showed that different visitor background will have a different level of awareness on those safety instructions.